Pelatihan Standar Penanganan Pangan Rendang di Sentra Produksi Randang - Reinny Patrisina; Prima Fithri; Lusi Susanti; Hilma Raimona Zadry; Difana Meilani; Eri Wirdianto; Jonrinaldi Jonrinaldi; Desto Jumeno; Asmuliardi Muluk; Alexie Herryandie; Feri Afrinaldi; Henmaidi Henmaidi; Alfadhlani Alfadhlani; Insannul Kamil; Dicky Fatrias; Taufik Taufik; Wisnel Wisnel; Alizar Hasan; Rika Ampuh Hadiguna; Ahmad Syafruddin; Nilda Tri Putri; Elita Amrina; Ikhwan Arief; Afri Adnan (Warta Pengabdian Andalas, 2019)
Nowadays, consumers are getting smarter in choosing products, including food products. Food safety is an important thing that must be considered by the food industry. Unsafe food production can only be done because of food, product needs, lengthy legal process, but can also damage the community. Customer needs demand certainty from the food provided in a way that meets food safety standards, from the garden to the table. To fulfill this reason, all parties involved in the food production process must know and understand well matters related to food procurement standards for the products produced. Rendang is one of the traditional foods of West Sumatra that has begun worldwide. This requires the need to produce rendang with food safety standards is very important. Based on this, within the framework of the Community Service Department of Industrial Engineering UNAND conducts training / technical guidance related to the rendang food procurement standards with training on Good Manufacturing Practices (GMP). This activity was expected to help Small and Medium Enterprises to get business standardization.